Pre-attendance analgesia advice for small acute paediatric burns in the British Isles: A National Survey. Issue 6 (September 2020) - Chu, Howard; Sen, Sankhya
Highlights: A national telephone survey of all paediatric burns services within the British Isles was conducted. Information gained on how each unit manages new referrals of small acute burns in children. 5% total body surface area burns should be the upper limit of new referrals accepted to be seen in an outpatient setting. Analgesia be given 60 min prior to an allocated appointment time. A qualified play specialist should be available to provide distraction whenever possible. Abstract: The development of acute outpatient clinics has enabled burns services to assess the majority of smaller paediatric burns the day after injury. This event can be distressing and it is therefore important to ensure that children are initially assessed in an optimal environment. The aim of this study is to understand how small acute paediatric burns are managed across the British Isles. All paediatric burns services within the British Isles were contacted by telephone and information gained on how each unit manages new referrals of small acute paediatric burns in an outpatient setting. This national survey has shown that 5% total body surface area (TBSA) is generally considered to be the upper limit for new paediatric referrals to be seen in the outpatient setting 5%. Furthermore, we advocate that Paracetamol and Ibuprofen be given 60 min prior to an allocated appointment time.